Mycobacterium leprae genomes from naturally infected nonhuman primates. - Tanvi P Honap; Luz-Andrea Pfister; Genevieve Housman; Sarah Mills; Ross P Tarara; Koichi Suzuki; Frank P Cuozzo; Michelle L Sauther; Michael S Rosenberg; Anne C Stone (Public Library of Science (PLoS), 2018)
Leprosy is caused by the bacterial pathogens Mycobacterium leprae and Mycobacterium lepromatosis. Apart from humans, animals such as nine-banded armadillos in the Americas and red squirrels in the British Isles are naturally infected with M. leprae. Natural leprosy has also been reported in certain nonhuman primates, but it is not known whether these occurrences are due to incidental infections by human M. leprae strains or by M. leprae strains specific to nonhuman primates. In this study, complete M. leprae genomes from three naturally infected nonhuman primates (a chimpanzee from Sierra Leone, a sooty mangabey from West Africa, and a cynomolgus macaque from The Philippines) were sequenced. Phylogenetic analyses showed that the cynomolgus macaque M. leprae strain is most closely related to a human M. leprae strain from New Caledonia, whereas the chimpanzee and sooty mangabey M. leprae strains belong to a human M. leprae lineage commonly found in West Africa. Additionally, samples from ring-tailed lemurs from the Bezà Mahafaly Special Reserve, Madagascar, and chimpanzees from Ngogo, Kibale National Park, Uganda, were screened using quantitative PCR assays, to assess the prevalence of M. leprae in wild nonhuman primates. However, these samples did not show evidence of M. leprae infection. Overall, this study adds genomic data for nonhuman primate M. leprae strains to the existing M. leprae literature and finds that this pathogen can be transmitted from humans to nonhuman primates as well as between nonhuman primate species. While the prevalence of natural leprosy in nonhuman primates is likely low, nevertheless, future studies should continue to explore the prevalence of leprosy-causing pathogens in the wild.